Maternal pesticide exposure and child neuro-development among smallholder tomato farmers in the southern corridor of Tanzania - Peter M. Chilipweli; Aiwerasia Vera Ngowi; Karim Manji (BMC, 2021)
Abstract Background Exposure to pesticides with its associated effects prenatally and in early childhood has not received much attention. There is little scientific data on this aspect in Tanzania therefore this study was meant to contribute to the deficit in the subject. Method A cross-sectional study was conducted to a sample of 286 participants of mother to child pair, whereby 172 and 114 were exposed and non-exposed respectively. Mothers who had been working in tomato sprayed farms were exposed and mothers who had not been working in the tomato sprayed farms were un-exposed. Child aged 0-6 years was chosen from each mother sampled but only one child found to be the youngest with the classified age was enrolled. Malawi child development Tool (M-DAT) was employed to assess the child level of development, height, and weight of the children were collected and analyzed by the WHO anthropometric calculator. A checklist and questionnaire were used to observe and assess maternal exposure. Bivariate and Multivariate analysis were conducted to assess the relationship between various factors of exposure. Results Overall 15% of the children examined were not well developed and the most used pesticides were those posing neuro-development effects. On the bivariate analysis model, mothers who worked while pregnant were more likely to have a child with neuro-developmental effect OR=5.8(1.29-26.3). On multivariate analyses adjusted for age of the mother, variables which remain in the model were a distance from home [AOR=9.4(4.2-20.5)], and working while pregnancy [AOR=5.8(1.29-26.3)] other were removed due to collinearity effect. None of confounders had a potential significant effect but only nutrition seems to be the effect modifier [AOR=7.8(1.29-36.3)] when analyzed with working while pregnancy. Conclusions The findings from this study have indicated that maternal pesticide exposure among farmworker residents in the SAGCOT area has a potential association with child developmental effect.